Efektivitas Kombinasi Ekstrak Kayu Manis (Cinnamomum burmannii) dan Mikroalga (Haematococcus pluvialis) sebagai Krim Tabir Surya: Formulasi, Uji In Vitro, dan In Vivo - Indarto, Indarto; Isnanto, Taufik; Muyassaroh, Farida; Putri, Imelda (Pusat Penelitian dan Pengembangan Biomedis dan Teknologi Dasar Kesehatan, 2022)
Indonesia is a tropical country with high intensity of sunlight. Exposure to high ultraviolet rays from sunlight on the skin for a long period of time brings negative impacts such as sunburn, erythema, and skin cancer. Counteracting the negative effects of sun exposure, natural sunscreens that are less toxic such as combination of Cinnamomum burmannii and Haematococcus pluvialis extracts are needed. Cinnamaldehyde as the high active compound in cinnamon extract is able to absorb UV-B rays due to a chromophore group in the form of an aromatic ring conjugated to carbonyl group, along astaxanthin content in the Haematococcus pluvialis which is able to ward off free radicals and has an anti-inflammatory function that the combination will be an effective sunscreen active ingredients. The study aims to develop an oil-in-the-water emulsion-type cream that is added as an active ingredient in a combination of Haematococcus pluvialis and Cinnamomum burmannii extracts to produce a sunscreen cream. The combination extracts was tested in vitro with a UV-Vis spectrophotometer and the SPF value. The cream was physically evaluated including homogeneity, spreadability, adhesion, viscosity, pH, and organoleptic tests as well as in vivo test using mice (Mus muculus). The results indicated that the cream formulas qualified for the physical standards, yet the viscosity value unqualified the standard . The in vitro test showed that the highest SPF value reached SPF 12 for the S2 formula with maximum category. In vivo test showed that the entire formula could protect the skin from exposure to UV-B rays by exoterra lamps.